Electrical Resistivity Imaging and the Saline Water Interface in High-Quality Coastal Aquifers - Costall, A.; Harris, Brett; Pigois, J. (Springer, 2018)
© 2018 The Author(s) Population growth and changing climate continue to impact on the availability of natural resources. Urbanization of vulnerable coastal margins can place serious demands on shallow groundwater. Here, groundwater management requires definition of coastal hydrogeology, particularly the seawater interface. Electrical resistivity imaging (ERI) appears to be ideally suited for this purpose. We investigate challenges and drivers for successful electrical resistivity imaging with field and synthetic experiments. Two decades of seawater intrusion monitoring provide a basis for creating a geo-electrical model suitable for demonstrating the significance of acquisition and inversion parameters on resistivity imaging outcomes. A key observation is that resistivity imaging with combinations of electrode arrays that include dipole–dipole quadrupoles can be configured to illuminate consequential elements of coastal hydrogeology. We extend our analysis of ERI to include a diverse set of hydrogeological settings along more than 100 km of the coastal margin passing the city of Perth, Western Australia. Of particular importance are settings with: (1) a classic seawater wedge in an unconfined aquifer, (2) a shallow unconfined aquifer over an impermeable substrate, and (3) a shallow multi-tiered aquifer system over a conductive impermeable substrate. We also demonstrate a systematic increase in the landward extent of the seawater wedge at sites located progressively closer to the highly urbanized center of Perth. Based on field and synthetic ERI experiments from a broad range of hydrogeological settings, we tabulate current challenges and future directions for this technology. Our research contributes to resolving the globally significant challenge of managing seawater intrusion at vulnerable coastal margins.